Producción de furfural a partir de bagazo de caña (2021)
The objective of this project was to evaluate the production of furfural from sugarcane bagasse obtained as a by-product of the Colombian sugar industry. Bagasse is usually used as a source of energy in factories; however, it can be used to produce higher value-added products such as furfural. Considering that bagasse is a good source of pentosan (around 25 to 27%). Furfural is an important organic chemical, produced from agro-industrial wastes and residues containing carbohydrates, and is known as furfuraldehyde. It is a basic chemical, which can be used in a variety of industries such as the chemical, petroleum refining industry, mainly.